2020
DOI: 10.15252/embr.201949762
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids limit lipopolysaccharide‐induced lethal inflammation by a double control system

Abstract: Lipopolysaccharides (LPS) can lead to a lethal endotoxemia, which is a systemic inflammatory response syndrome (SIRS) characterized by a systemic release of cytokines, such as TNF. Endotoxemia is studied intensely, as a model system of Gram-negative infections. LPS-and TNF-induced SIRS involve a strong induction of interferon-stimulated genes (ISGs), some of which cause cell death in the intestinal epithelium cells (IECs). It is well known that glucocorticoids (GCs) protect against endotoxemia. By applying num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Upon administration of a high dose of ligand, these half-sites appear to be vacated and the monomers are recuperated as GR dimers binding on full GRE motifs. The GR dim mutant has been shown to bind the GRE element with lower affinity than the GR wt , because the monomers of the GR dim mutant have a reduced cooperativity when binding DNA as mentioned before [ 61 ] and/or because the GR dim is deficient in complex formation as recently shown [ 79 ]. Interestingly, it has been demonstrated in vitro that GR wt is fully responsive, the GR dim mutant has a reduced transcriptional response, and the GR mon mutant does not respond upon administration of GCs [ 120 ].…”
Section: Gr Dimer and Monomer Transcriptional Regulationmentioning
confidence: 97%
See 1 more Smart Citation
“…Upon administration of a high dose of ligand, these half-sites appear to be vacated and the monomers are recuperated as GR dimers binding on full GRE motifs. The GR dim mutant has been shown to bind the GRE element with lower affinity than the GR wt , because the monomers of the GR dim mutant have a reduced cooperativity when binding DNA as mentioned before [ 61 ] and/or because the GR dim is deficient in complex formation as recently shown [ 79 ]. Interestingly, it has been demonstrated in vitro that GR wt is fully responsive, the GR dim mutant has a reduced transcriptional response, and the GR mon mutant does not respond upon administration of GCs [ 120 ].…”
Section: Gr Dimer and Monomer Transcriptional Regulationmentioning
confidence: 97%
“…Indeed, we recently showed that GCs apply two key mechanisms to control endotoxemia. One at the level of macrophages, where GCs are thought to suppress TNF production in a GR monomer-dependent way, and one at the level of the intestinal epithelium, where GCs are believed to suppress TNFR1-induced ISG gene expression and necroptotic cell death in a dimer-dependent way [ 61 ]. Lastly, Osteopontin (OPN), a crucial mediator for lung inflammation, is increased in the lungs of GR dim/dim mice challenged with LPS compared to GR wt/wt mice.…”
Section: Role Of Gr Complex Formation In Sirs and Sepsismentioning
confidence: 99%
“…The pictures display typical examples and reveal that (i) untreated mice or Zn‐treated mice show normal numbers of granules, normal endoplasmic reticulum (ER) structure, normal lumen size, and no cells extruded, no small apoptotic bodies; (ii) the devastating effects of TNF on Paneth cells as reflected by cell swelling, loss of granules, dark and swollen ER, many big apoptotic bodies, big lysosomes toward the lumen, extrusion of cells into the lumen, and loss of contact with the basal membrane; (iii) we observe that Zn is able to confer protection against these features to some extent, and the general morphology of the Paneth cells is in between control and TNF situation. Finally, we performed qPCR on ileum samples to detect Paneth cell‐specific markers, the decline of which being a readout of less PCs, as described in the literature (Van Looveren et al , ). The expression of Defa6 and Lyz1 , two Paneth cell markers, is shown in Fig D and E, and the data confirm that PC numbers decline by TNF, but significantly less by Zn treatment.…”
Section: Resultsmentioning
confidence: 99%
“…As described recently (Van Looveren et al , ), death of Paneth cells was quantified by measuring the expression of typical Paneth cell genes, by qPCR, i.e., Defa6 and Lyz1 .…”
Section: Methodsmentioning
confidence: 99%
“…Since inflammation is able to induce the stabilization and activation of HIF (Cummins et al, 2016), it would be of great interest to know whether HIF might play a role in the GCR during sepsis. The protective effects of exogenous GCs like DEX against LPS-induced endotoxemia are frequently associated with the inhibition of TNF production in white blood cells, such as macrophages (Bhattacharyya et al, 2007;Kleiman et al, 2012;Van Looveren et al, 2020). Nevertheless, hepatic GR is also crucial for the GC homeostasis and the protection against SIRS and sepsis ( Van Bogaert et al, 2011;Jenniskens et al, 2018).…”
Section: Discussionmentioning
confidence: 99%